Analysis of Marriage Legalization Decisions at the Bulukumba Religious Court from a Progressive Law Perspective - Jamin, Awaluddin; Muhammad Saleh Ridwan; Asni, Asni; Imran Anwar Kuba; Rian Hidayat (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the judge’s considerations in marriage legalization (isbat nikah) cases in the Bulukumba Religious Court from the perspective of progressive legal theory. It employs field research using statutory, sociological, and legal anthropological approaches to understand the dynamics of legal reasoning within the context of social reality and substantive justice. The findings indicate that in deciding marriage legalization cases, judges refer to Law Number 1 of 1974 on Marriage and the Compilation of Islamic Law (Presidential Instruction Number 1 of 1991), by assessing the validity of the marriage pillars and conditions, as well as their conformity with both Islamic and positive law provisions. Analysis of Decision No. 315/Pdt.P/2023/PA.Blk and No. 297/Pdt.P/2023/PA.Blk reveals that judges have taken into account the values of justice in the spirit of progressive law, which views law as a means of social transformation for the benefit of society. Progressive law is understood as a dynamic legal concept that prioritizes substantive justice and responds to the legal needs of society to achieve legal certainty while protecting citizens’ rights.